2017
DOI: 10.1007/s11356-017-0953-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of zinc oxide nanoparticles on lettuce (Lactuca sativa L.) growth and soil bacterial community

Abstract: The wide spread of nanoparticles (NPs) has caused tremendous concerns on agricultural ecosystem. Some metallic NPs, such as zinc oxide (ZnO), can be utilized as a nano-fertilizer when used at optimal doses. However, little is known about the responses of plant development and concomitant soil bacteria community to ZnO NPs. The present pot experiment studied the impacts of different doses of ZnO NPs and bulk ZnO (0, 1, 10, 100 mg ZnO/kg), on the growth of lettuce (Lactuca sativa L.) and the associated rhizosphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(48 citation statements)
references
References 49 publications
2
39
0
Order By: Relevance
“…In lettuce, the growth and biomass increased on exposure to phytosynthesized ZnO nanoparticles [51]. Engineered ZnO nanoparticles increased the fresh/dry weight of leaves and roots in coffee plant [52]. Engineered ZnO nanoparticles increased the germination and root growth of maize and cabbage [53].…”
Section: Impact Of Silver Nanoparticles and Silver Nitrate On The Biomentioning
confidence: 99%
“…In lettuce, the growth and biomass increased on exposure to phytosynthesized ZnO nanoparticles [51]. Engineered ZnO nanoparticles increased the fresh/dry weight of leaves and roots in coffee plant [52]. Engineered ZnO nanoparticles increased the germination and root growth of maize and cabbage [53].…”
Section: Impact Of Silver Nanoparticles and Silver Nitrate On The Biomentioning
confidence: 99%
“…The thermally unstable nature of allium bioactive constituents [16,20] also affects their application in feed production, since thermal processing is an important step to decontaminate the harmful microorganisms of feed. The OSCs have poor water solubility [125], which further limits their application in feed. While considering these factors, the higher cost of allium-based feed cannot be overlooked.…”
Section: Factors Determining the Effectiveness Of Alliums In Poultry mentioning
confidence: 99%
“…Sundari et al [149] reported turmeric extract nanoparticle as a feed additive which improved meat quality at low dosage without affecting performance in broilers. Xu et al [125] converted natural organosulfur compounds into nanometer-sized iron sulfides (nFeS) with improved antibacterial activity and antibiofilm efficacy in vitro. Jini and Sharmila [150] synthesized silver nanoparticles from A. cepa, which have higher in vitro antidiabetic and antioxidant activities.…”
Section: Microencapsulation/nanotechnologymentioning
confidence: 99%
“…Metallic NPs have cumulative ion release compared to a constant supply of ions from their bulky counterparts. The former pattern of ion release is more efficient because it provides a continuous leaking of ions from particles (Xu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%